Améliorer la qualité du travail dans les services en Europe - Vassil Kirov (La Nouvelle Revue du Travail)
The article explores the role that institutional clients play in determining service sector employees’ quality of work. Based on triangulation analysis in the sociology of work, specific hypothesis are formulated in relation to ‘dedicated’ institutional customer services. Interviews and case studies conducted in different European countries are used to analyse how “customers” affect the stability of employment, working times and professionalisation – as well as the way social partners apprehend these impacts in an attempt to safeguard working conditions.